Thermosetting resin composition, resin adhesive film and application thereof

Through the combination of benzocyclobutene resin with a specific structure, components containing C=C unsaturated bonds and modified inorganic fillers, the existing resistance of existing resin materials in the development of high frequency, high speed and high reliability is solved. The problem of insufficient thermal properties and need to be improved in dielectric performance has achieved low dielectric loss and excellent dielectric stability, and met the performance requirements of high-frequency and high-speed printed circuit boards.

CN119490631AActive Publication Date: 2025-02-21GUANGDONG SHENGYI SCI TECH

Patent Information

Application Number
CN202311026671.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

In the development of high frequency and high speed and high reliability, existing resin materials have problems such as insufficient heat resistance, high dielectric constant and dielectric loss, large brittleness, short storage period and need to improve dielectric performance.

Method used

The benzocyclobutene resin with a specific structure, components containing C=C unsaturated bonds, and inorganic fillers surface-treated with unsaturated group-containing coupling agent are combined to form excellent dielectric properties and consistent interfaces. a thermosetting resin composition.

Benefits of technology

It achieves low dielectric loss, excellent dielectric stability and high binding force, and meets the performance requirements of high-frequency and high-speed printed circuit boards, and maintains good dielectric performance especially under HAST conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490631A_ABST
    Figure CN119490631A_ABST
Patent Text Reader

Abstract

The invention provides a thermosetting resin composition, a resin adhesive film and application thereof. The thermosetting resin composition comprises the following components in parts by mass: 5-95 parts of benzocyclobutene resin, 5-95 parts of a component containing C = C unsaturated bonds, 5-300 parts of a modified filler and 0.1-10 parts of an initiator, the modified filler is an inorganic filler subjected to surface treatment by a coupling agent containing unsaturated groups, and the unsaturated groups are selected from any one or a combination of at least two of styryl, acryloyloxy, methacryloyloxy and polybutadiene groups. A resin adhesive film prepared from the thermosetting resin composition is excellent in dielectric property, low in dielectric loss tangent Df, good in dielectric stability, small in Df (10GHz) variation amplitude after HAST, high in chemical copper binding force and capable of fully meeting the performance requirement for preparing a high-frequency and high-speed printed circuit board through a semi-addition method or an addition method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor materials, and in particular relates to a thermosetting resin composition, a resin film and applications thereof. Background Art

[0002] In recent years, electronic equipment has gradually developed towards miniaturization and high performance. As an important electronic component in electronic equipment, printed circuit boards are also faced with the development requirements of stacking layer multilayering, fine wiring, high density, high frequency, high speed and high reliability. As the manufacturing technology of printed circuit boards, it is known that the manufacturing method of the stacking (build up) mode in which insulating layers and conductor layers are alternately overlapped on inner substrates includes semi-additive method and additive method etc. Insulating layer is usually formed by curing with resin combination. On the one hand, in order to match the high frequency, high speed and high reliability development of printed circuit boards, insulating layer is required to have excellent heat resistance, moisture and heat resistance and dimensional stability, and has low dielectric constant and low dielectric loss. On the other hand, based on the process needs of stacking (build up) technology and ultra-fine circuits, insulating layer and conductor layer (metal layer) are required to have higher bonding force.

[0003] Generally speaking, the resin composition for preparing the insulating layer includes resin and inorganic filler. Usually, in order to meet the performance requirements of low thermal expansion coefficient (CTE) and low warpage of the insulating layer, it is necessary to use a highly filled inorganic filler with a mass content of more than 30wt% in the resin composition. However, the highly filled inorganic filler will reduce the moisture and heat resistance of the insulating layer, making the board perform poorly in the HAST (Highly Accelerated Temperature and Humidity Stress Test) test. In addition, in order to improve the dispersibility of the inorganic filler in the resin, the industry usually selects an appropriate surface treatment agent to perform surface treatment on it, but the surface treatment of the inorganic filler will have a greater adverse effect on the final dielectric properties and dielectric reliability of the resin composition and the insulating layer.

[0004] As for the resin materials for preparing the insulating layer, the types that are currently considered in the industry to be able to meet the basic performance requirements of printed circuit boards include thermosetting polyphenylene ether resins, bismaleimide resins, hydrocarbon resins, etc. However, with the development of high frequency, high speed and high reliability of printed circuit boards, some performance defects of existing resins have attracted attention in the industry, such as the high dielectric constant and dielectric loss of thermosetting polyphenylene ether resin cured products; the brittleness of bismaleimide resins is large, the storage period is short, and there is still room for improvement in dielectric properties; hydrocarbon resins have insufficient heat resistance, a large thermal expansion coefficient, and dimensional stability that makes it difficult to meet the performance requirements of high-performance electronic equipment for printed circuit boards.

[0005] Benzocyclobutene is a type of thermosetting material with an all-carbon-hydrogen structure. Due to its excellent heat resistance, mechanical properties, extremely low dielectric loss, extremely low dielectric constant and low cost, it is expected to be used as a new generation of high-performance electronic materials in the field of high-end microelectronics. Benzocyclobutene is a volatile liquid with a low boiling point of about 150°C. It is generally prepared as a derivative for use. Benzocyclobutene can react with vinyl at high temperatures to form a cyclohexane structure, or dimerize to a cyclooctane structure at higher temperatures, thereby achieving higher heat resistance. Benzocyclobutene derivatives are usually small molecules, generally containing more than two benzocyclobutene functional groups, and can further form polymers under high temperature conditions. The following methods are currently known for preparing benzocyclobutene derivatives: (1) Heck coupling reaction of 4-bromobenzocyclobutene and tetramethyldivinyldisiloxane to obtain siloxane-containing dibenzocyclobutene; (2) etherification reaction of 4-bromobenzocyclobutene and resorcinol under the catalysis of cuprous chloride to prepare dibenzocyclobutene derivatives containing phenyl ether and naphthoic acid structures. The above materials have excellent heat resistance and mechanical properties, but the molecular structure contains siloxane or phenol groups, not a full carbon-hydrogen structure, and it is difficult to obtain low dielectric properties. (3) Suzuki coupling reaction of 4-bromobenzocyclobutene and phenylboronic acid to prepare derivatives with a full carbon-hydrogen structure, but the cost of phenylboronic acid is relatively high, and the residual polar boric acid or boric acid end group will cause serious attenuation of dielectric properties. (4) Divinylbenzene and benzocyclobutene undergo Heck coupling reaction to prepare derivatives with an all-carbon-hydrogen structure. However, divinylbenzene can undergo free radical polymerization at room temperature and easily generate by-products, making mass production difficult.

[0006] In general, the existing manufacturing process is very likely to sacrifice the original dielectric advantages of the benzocyclobutene structure, resulting in the performance of the benzocyclobutene structure being difficult to exert in the printed circuit board and the insulating layer; moreover, the high filling of inorganic fillers in the insulating layer will also have an adverse effect on the dielectric properties, dielectric stability, and bonding strength between the insulating layer and the metal layer of the board. Therefore, it is an urgent problem to be solved in this field to develop a resin material with excellent dielectric properties and dielectric stability, so that it still maintains low dielectric loss after HAST, has good reliability, and has high bonding strength with the metal conductor layer, so as to meet the requirements of preparing high-frequency and high-speed printed circuit boards by semi-additive or additive methods. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a thermosetting resin composition, a resin film and applications thereof. A benzocyclobutene resin with a specific structure, a component containing a C=C unsaturated bond and an inorganic filler surface-treated with an unsaturated group coupling agent are compounded with each other. On the one hand, the thermosetting resin composition has excellent dielectric properties. On the other hand, a bridging effect is formed between the interface of the organic resin component and the inorganic filler, so that the interface consistency of the cured product is good, so that the resin film formed by the thermosetting resin composition has low dielectric loss and excellent dielectric stability, still maintains low dielectric loss after HAST, and has strong bonding with the metal layer, which fully meets the requirements of preparing high-frequency and high-speed printed circuit boards by semi-additive method or additive method.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a thermosetting resin composition, wherein the thermosetting resin composition comprises the following components in parts by mass:

[0010]

[0011] The modified filler is an inorganic filler that has been surface-treated with an unsaturated group-containing coupling agent, wherein the unsaturated group in the unsaturated group-containing coupling agent is selected from any one of styrene, acryloxy, methacryloxy, and polybutadiene groups, or a combination of at least two thereof;

[0012] The benzocyclobutene resin comprises at least one structural unit A and at least one structural unit B;

[0013] The structural unit A has a structure as shown in Formula I:

[0014]

[0015] In formula I, R1 is vinylene and / or ethylene.

[0016] The structural unit B has a structure as shown in Formula II:

[0017]

[0018] In formula II, R2 is vinyl, ethyl and / or phenyl.

[0019] In the benzocyclobutene resin of the present invention, the side chain of the structural unit A contains a benzocyclobutene structure, and the structural unit B is any one of a polybutadiene structure, a hydrogenated polybutadiene structure, and a polystyrene structure, or a combination of at least two thereof; the benzocyclobutene resin is a full carbon-hydrogen structure, has a low dielectric constant Dk and a low dielectric loss tangent Df, and has low polarity and low water absorption; at the same time, the molecular structure contains an easily reactive alkenyl group (an alkenyl group from polybutadiene, a benzocyclobutene ring with C=C formed by thermal ring opening), and better dielectric properties can be obtained by thermal curing; and the resin structure contains a plurality of benzocyclobutene functional groups, and can be thermally cured to obtain a high crosslinking density, a high glass transition temperature, and excellent heat resistance.

[0020] The modified filler is an inorganic filler that has been surface-treated with a coupling agent containing an unsaturated group. The surface of the inorganic filler carries a specific type of unsaturated group, and the unsaturated group plays a bridging role on the interface between the resin system and the inorganic filler, especially forming a chemical bond bridge at the interface between the component containing the C=C unsaturated bond, the benzocyclobutene resin and the inorganic filler. The interface consistency after cross-linking and curing is good, and low dielectric loss can be achieved.

[0021] In the thermosetting resin composition provided by the present invention, a benzocyclobutene resin with a specific structure, a component containing a C=C unsaturated bond, and an inorganic filler surface-treated with a coupling agent containing an unsaturated group are compounded. The ring-opening process of the benzocyclobutene structure is an endothermic reaction, which can adjust the curing temperature range of the system. At the same time, after the ring-opening, free radicals are formed by themselves, and the free radicals are combined with the component containing a C=C unsaturated bond and the inorganic filler surface-treated with a coupling agent containing an unsaturated group to form a cured product with excellent interface consistency under the action of an initiator. The thermosetting resin composition and the resin film containing the thermosetting resin composition have a high degree of crosslinking, so that the thermosetting resin composition and the resin film containing the thermosetting resin composition have a sufficiently low dielectric loss tangent Df, excellent dielectric properties, low water absorption, excellent heat resistance, dielectric stability and reliability, and can still maintain a low dielectric loss tangent Df after HAST, and have a high modulus. The formed resin film has a low roughness after Desmear treatment and a high bonding strength (chemical copper bonding strength) with the metal layer, which fully meets the performance requirements of preparing high-frequency and high-speed printed circuit boards by semi-additive or additive methods.

[0022] In the thermosetting resin composition provided by the present invention, the benzocyclobutene resin is 5-95 parts, for example, it can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, preferably 20-80 parts.

[0023] The component containing C=C unsaturated bonds is 5-95 parts, for example, it can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, preferably 20-80 parts.

[0024] The modified filler is 5-300 parts, for example, it can be 10 parts, 30 parts, 50 parts, 80 parts, 100 parts, 120 parts, 150 parts, 180 parts, 200 parts, 220 parts, 250 parts or 280 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, preferably 40-300 parts.

[0025] The initiator is 0.1-10 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, preferably 0.2-5 parts.

[0026] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.

[0027] As a preferred technical solution of the present invention, the unsaturated group-containing coupling agent is a silane coupling agent containing unsaturated groups.

[0028] Preferably, the unsaturated group-containing coupling agent includes any one of a styrene-containing silane coupling agent, an acryloxy-containing silane coupling agent, a methacryloxy-containing silane coupling agent, a butadiene polymer-modified silane coupling agent, and a styrene-butadiene polymer-modified silane coupling agent, or a combination of at least two thereof.

[0029] In the present invention, the unsaturated group-containing coupling agent can be purchased from the market. For example, the styrene-containing silane coupling agent includes p-styrene trimethoxy silane (Shin-Etsu Chemical KBM-1403); the methacryloxy-containing silane coupling agent includes 3-methacryloxypropyl methyl dimethoxy silane (KBM-502), 3-methacryloxypropyl trimethoxy silane (KBM-503), 3-methacryloxypropyl methyl diethoxy silane (KBE-502), 3-methacryloxypropyl triethoxy silane (KBE-503). , 8-methacryloyloxyoctyltrimethoxysilane (KBM-5803), silane coupling agent X-40-9296, any one or a combination of at least two; the acryloxy-containing silane coupling agent includes 3-acryloyloxypropyltrimethoxysilane (KBM-5103), silane coupling agent X-12-1048, silane coupling agent X-12-1050, silane coupling agent KR-513, silane coupling agent X-40-2430C, any one or a combination of at least two; the styrene-butadiene polymer modified silane coupling agent includes X-12-1281C.

[0030] Exemplarily, the acryloxy-containing silane coupling agent contains a structure as shown in Formula S1:

[0031]

[0032] In formula S1, R S1 , R S2 Each is independently methyl or ethyl.

[0033] In formula S1, m and n are each independently selected from integers of 1-4, for example, 1, 2, 3 or 4.

[0034] In formula S1, K and L represent the number of repeating units, and are independently selected from integers of 1-30, for example, 2, 3, 4, 8, 10, 12, 15, 18, 20, 22, 25 or 28, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values ​​included in the range, and 1-10 is further preferred.

[0035] In formula S1, the linking order of each repeating unit is arbitrary.

[0036] Preferably, the number of fluorine atoms in the acryloxy silane coupling agent of the structure shown in Formula S1 is 3-30, for example 3, 6, 9, 12, 15, 18, 21, 24, 27 or 30, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0037] Preferably, the number of acryloxy groups in the acryloxy-containing silane coupling agent having the structure shown in Formula S1 is 1-10, for example, 2, 3, 4, 5, 6, 7, 8 or 9.

[0038] Preferably, the acryloxy-containing silane coupling agent having the structure shown in Formula S1 is a commercially available product, such as X-40-2430C produced by Shin-Etsu Chemical.

[0039] Exemplarily, the styrene-butadiene polymer modified silane coupling agent has a structure as shown in Formula S2:

[0040]

[0041] In formula S2, R S3 , R S4 Each is independently selected from any one of C1-C10 (eg, C2, C3, C4, C5, C6, C7, C8, etc.) straight chain or branched chain alkyl, C6-C10 (eg, C6, C9, etc.) aryl.

[0042] In formula S2, t is an integer of 1-3, for example, 1, 2 or 3; when t≥2, multiple (2 or 3) OR S3 are the same or different groups; when t is 1, multiple (2 or 3) R S4 are the same or different groups.

[0043] When t is 3, it means there are 3 -OR connected to Si. S3 Group, R S4 Does not exist.

[0044] In formula S2, e, f, g, and h represent the number of repeating units, and are independently selected from integers of 1-40, for example, 2, 3, 4, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 35, 35 or 38, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0045] In formula S2, the linking order of each repeating unit is arbitrary.

[0046] Preferably, the number average molecular weight of the styrene-butadiene polymer modified silane coupling agent of the structure shown in Formula S2 is 500-50000, for example, it can be 800, 1000, 3000, 5000, 8000, 10000, 12000, 15000, 18000, 20000, 25000, 30000, 35000, 40000 or 45000, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 1000-20000 is further preferred.

[0047] Preferably, in the present invention, the number average molecular weight of the material is tested by gel permeation chromatography (GPC) method based on polystyrene calibration according to the description in GB / T 21863-2008.

[0048] Preferably, the styrene-butadiene polymer modified silane coupling agent with the structure shown in Formula S2 is a commercially available product, such as Shin-Etsu Chemical X-12-1281C.

[0049] In the present invention, the method of surface treating the inorganic filler with the unsaturated group-containing coupling agent to obtain the modified filler may be any surface treatment method known in the prior art.

[0050] Illustratively, the modified filler is prepared by the following method, which includes: placing an inorganic filler in a stirring device, adding an unsaturated group-containing coupling agent thereto under stirring, and performing surface treatment to obtain the modified filler.

[0051] Preferably, the surface treatment time is 1-60 min, for example, it can be 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min or 55 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Preferably, based on the mass of the inorganic filler as 100%, the mass of the unsaturated group-containing coupling agent is 0.1-5.0%, for example, it can be 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] As a preferred technical solution of the present invention, the mass of the unsaturated group-containing coupling agent is 0.1-5.0% based on 100% of the inorganic filler, so that the inorganic filler is fully surface treated, so that the modified filler obtained contains an appropriate amount of unsaturated groups, plays a bridging role between the inorganic filler and the resin system, and crosslinks and cures with the benzocyclobutene resin and the component containing the C=C unsaturated bond, so that the interface consistency of the cured product is good, and has excellent dielectric properties and dielectric stability. If the mass of the unsaturated group-containing coupling agent is too low, the surface treatment of the inorganic filler is insufficient, and a uniform coating cannot be formed, resulting in a weak bridging effect between the inorganic filler and the resin system, which affects the dielectric properties of the cured product and the bonding strength with the metal layer. If the mass of the unsaturated group-containing coupling agent is too high, the excess unsaturated group-containing coupling agent will undergo free migration, which will also affect the bonding strength between the cured product and the metal layer. Its copper bonding strength as the surface of the resin film is low, and the dielectric properties of the resin film will be reduced at the same time.

[0054] In the present invention, the inorganic filler includes any one of non-metallic oxides, metal oxides, metal hydroxides, metal nitrides, non-metallic nitrides, inorganic hydrates, inorganic salts, metal hydrates, and inorganic phosphorus, or a combination of at least two thereof.

[0055] Preferably, the inorganic filler includes any one of silicon dioxide, titanium dioxide, zinc oxide, aluminum hydroxide, aluminum oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, zirconium oxide, mica, boehmite, calcined talc, talc, silicon nitride, strontium titanate, barium titanate, and calcined kaolin, or a combination of at least two thereof.

[0056] The silica may be any one of fused silica, crystalline silica, spherical silica, hollow silica, or a combination of at least two thereof.

[0057] Preferably, the median particle size (D 50 ) is 0.01-10μm, for example, it can be 0.05μm, 0.1μm, 0.3μm, 0.5μm, 0.8μm, 1μm, 3μm, 5μm, 8μm or 9μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0058] For example, the particle size of the inorganic filler is measured using a MS3000 Malvern laser particle size analyzer.

[0059] Preferably, the molar percentage of structural unit A in the benzocyclobutene resin is ≥5%, for example, it can be 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific points included in the range, and it is further preferably ≥30%, and further preferably 30-60%.

[0060] As a preferred technical solution of the present invention, the molar percentage of the structural unit A in the benzocyclobutene resin is 30-60%. The higher the content of the structural unit A, the higher the content of the benzocyclobutene structure, and the more obvious the excellent dielectric properties, high heat resistance, and high modulus of the benzocyclobutene resin are. If the molar percentage of the structural unit A is too low, the heat resistance of the benzocyclobutene resin and the thermosetting resin composition containing it will be reduced, and the modulus and dielectric properties will also be weakened. If the molar percentage of the structural unit A is too high, it will not only bring higher synthesis difficulty (increased reaction temperature, prolonged reaction time, increased catalyst dosage, etc.) and production cost, but also reduce the crosslinking and curing degree of the benzocyclobutene resin and the thermosetting resin composition containing it, affecting the dielectric properties.

[0061] Preferably, the benzocyclobutene resin comprises a structural unit A1 (R1 is vinylidene) having the structure The molecular structure contains easily reactive vinylidene groups, which have high cross-linking efficiency in the thermal curing reaction and make the cured resin film have good elasticity.

[0062] Preferably, the benzocyclobutene resin comprises a structural unit A2 (R2 is ethylene), the structure of which is Optionally, the structural unit A2 can be obtained by hydrogenating the structural unit A1; the bridging group between the benzocyclobutene structure and the main chain is a saturated alkyl chain, and has good dielectric properties.

[0063] Preferably, the molar percentage of the structural unit B in the benzocyclobutene resin is 15-90%, for example, it can be 18%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0064] As a preferred technical solution of the present invention, the molar percentage of the structural unit A in the benzocyclobutene resin is 5-80%, more preferably 30-60%, and the molar percentage of the structural unit B is 15-90%, thereby making the benzocyclobutene resin have excellent dielectric properties, heat resistance, moisture and heat resistance, modulus and mechanical properties, and have high thermal curing cross-linking reaction activity and cross-linking density. If the molar percentage of the structural unit A is too low, the heat resistance and reactivity of the benzocyclobutene resin will be reduced; if the molar percentage of the structural unit A is too high, not only will the synthesis difficulty and production cost be increased, but also the flexibility of the benzocyclobutene resin will be reduced.

[0065] Preferably, the benzocyclobutene resin comprises a structural unit B1 (R2 is a vinyl group), the structure of which is The molecular structure contains easily reactive vinyl groups, which can react with components containing C=C unsaturated bonds, double bonds after ring opening of benzocyclobutene, and unsaturated groups in modified fillers to increase the crosslinking efficiency in the thermal curing reaction and the crosslinking density after curing.

[0066] Preferably, the benzocyclobutene resin comprises a structural unit B2 (R2 is ethyl), the structure of which is Optionally, the structural unit B2 can be obtained by hydrogenating the structural unit B1, which contains a saturated alkyl structural unit and has low dielectric loss.

[0067] Optionally, the structural unit A2 can be obtained by hydrogenating the structural unit A1, and the structural unit B2 can be obtained by hydrogenating the structural unit B1; the introduction of the hydrogenated structural unit A2 and / or structural unit B2 is helpful to further optimize the dielectric properties of the benzocyclobutene resin and the resin composition. It should be noted that when R1 of the structural unit A in the benzocyclobutene resin is vinylidene, R2 of the structural unit B can be vinyl or ethyl; similarly, when R1 of the structural unit A in the benzocyclobutene resin is ethylene, R2 of the structural unit B can be vinyl or ethyl. In other words, the polybutadiene double bonds in the structural unit A and the structural unit B in the benzocyclobutene resin may not be hydrogenated, may be partially hydrogenated, or may be fully hydrogenated.

[0068] Preferably, the benzocyclobutene resin comprises a structural unit B3 (R2 is a phenyl group), the structure of which is

[0069] Preferably, the benzocyclobutene resin further comprises a structural unit C, wherein the structural unit C has a structure as shown in Formula IIIA and / or Formula IIIB:

[0070]

[0071] It should be noted that the benzocyclobutene resin is a polymer segment structure, including at least one (preferably multiple) structural unit A, at least one (preferably multiple) structural unit B and optionally a structural unit C; the present invention does not limit the connection sequence of the above structural units, and any connection sequence / connection method feasible in chemistry is within the scope of the present invention.

[0072] Preferably, the molar percentage of the structural unit C in the benzocyclobutene resin is ≤40%, for example, it can be 0%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35% or 38%, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, and further preferably ≤30%, and further preferably ≤20%. Thus, the curing degree of the benzocyclobutene resin and the thermosetting resin composition containing the same is increased, and has a higher glass transition temperature, better heat resistance and moisture heat resistance.

[0073] Preferably, the number average molecular weight of the benzocyclobutene resin is 2200-20000, for example, it can be 2300, 3000, 5000, 8000, 10000, 12000, 15000 or 18000, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range, and 2500-20000 is further preferred.

[0074] Preferably, the component containing C=C unsaturated bonds includes a small molecule compound containing C=C unsaturated bonds and / or a resin containing C=C unsaturated bonds.

[0075] Preferably, the group containing a C═C unsaturated bond includes any one of vinyl, vinylphenyl, vinylbenzyl, allyl, (meth)acrylate, isopropenyl, and maleimide, or a combination of at least two of them.

[0076] Wherein, the (meth)acrylate group is an acrylate group and / or a methacrylate group.

[0077] In the present invention, the component containing C=C unsaturated bonds can be a small molecule compound and / or a resin (polymer), illustratively including but not limited to: a small molecule compound and / or a resin (polymer) containing any one or a combination of at least two of vinyl, vinylphenyl, vinylbenzyl, allyl, acrylate, methacrylate, isopropenyl, and maleimide groups.

[0078] Preferably, the component containing C=C unsaturated bonds includes any one of unsaturated polyphenylene ether, polybutadiene, styrene-butadiene copolymer, styrene-butadiene-styrene triblock copolymer, multifunctional vinyl aromatic polymer, vinyl alicyclic polymer, allyl compound, multifunctional vinyl compound, maleimide compound or a combination of at least two thereof.

[0079] Preferably, the unsaturated polyphenylene ether is a polyphenylene ether having a C=C unsaturated bond at the end group.

[0080] Preferably, the unsaturated polyphenylene ether includes polyphenylene ether whose terminal groups contain any one or at least two of vinylbenzyl, vinylphenyl, acrylate and methacrylate groups.

[0081] In the present invention, the polybutadiene, styrene-butadiene copolymer, and styrene-butadiene-styrene triblock copolymer all contain crosslinkable active groups C=C, which can be 1,2-vinyl based on butadiene monomers.

[0082] Preferably, the polybutadiene includes any one of unmodified polybutadiene, acrylate-modified polybutadiene, and methacrylate-modified polybutadiene, or a combination of at least two thereof.

[0083] In the present invention, the styrene-butadiene copolymer may be a styrene-butadiene random copolymer and / or a styrene-butadiene block copolymer.

[0084] Preferably, the polymerized monomers of the multifunctional vinyl aromatic polymer include a combination of a divinyl aromatic compound and a monovinyl aromatic compound.

[0085] Preferably, the divinyl aromatic compound includes any one of divinylbenzene, divinylbiphenyl, divinylnaphthalene, diisopropenylbenzene, diisopropenylnaphthalene, and diisopropenylbiphenyl, or a combination of at least two thereof; the above-mentioned divinyl aromatic compounds include all their isomers.

[0086] Preferably, the monovinyl aromatic compound includes styrene, and other monovinyl aromatic compounds except styrene.

[0087] In the present invention, the multifunctional vinyl aromatic polymer can be purchased from the market, such as the ODV series of Nippon Steel.

[0088] Preferably, the allyl compound includes any one of triallyl isocyanurate (TAIC), trimethallyl isocyanate (TMAIC), triallyl cyanurate (TAC), triallyl polyisocyanurate, triallyl cyanurate, and diallyl phthalate, or a combination of at least two thereof;

[0089] Preferably, the multifunctional vinyl compound includes any one of divinylbenzene (DVB), 1,2-bis(p-vinylphenyl)ethane (BVPE), and multifunctional (meth)acrylate, or a combination of at least two thereof.

[0090] Preferably, the maleimide compound includes any one of a monomaleimide compound, a bismaleimide compound, a multifunctional maleimide compound, and a maleimide resin, or a combination of at least two thereof.

[0091] Preferably, the component containing C=C unsaturated bonds includes any one or a combination of at least two of unsaturated polyphenylene ether, polybutadiene, styrene-butadiene copolymer, multifunctional vinyl aromatic polymer, and allyl compound, and further preferably a combination of at least two (e.g., 2, 3, 4 or 5).

[0092] Preferably, the thermosetting resin composition comprises 0-40 parts by mass of unsaturated polyphenylene ether, for example, 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0093] Preferably, the thermosetting resin composition includes 0-40 parts of polybutadiene by mass, for example, it can be 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts or 35 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0094] Preferably, the thermosetting resin composition includes 0-30 parts of styrene-butadiene copolymer in parts by mass, for example, it can be 1 part, 5 parts, 10 parts, 15 parts, 20 parts or 25 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0095] Preferably, the thermosetting resin composition comprises 0-50 parts by mass of a multifunctional vinyl aromatic polymer, for example, 1 part, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0096] Preferably, the thermosetting resin composition includes 0-20 parts of allyl compounds by mass, for example, 1 part, 3 parts, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts or 18 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0097] As a preferred technical solution of the present invention, in the thermosetting resin composition, based on the total mass of the benzocyclobutene resin and the component containing C=C unsaturated bonds as 100%, the mass of the modified filler is 30-300%, for example, it can be 50%, 80%, 100%, 120%, 150%, 180%, 200%, 220%, 250% or 280%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0098] The thermosetting resin composition provided by the present invention is preferably used as a resin film and as an insulating layer of a printed circuit board (PCB board), and a conductor layer (metal layer) is preferably formed on the insulating layer by an addition method or a semi-additive method. The use of a 30-300% high-filled modified filler can enable the resin film to meet the requirements of low thermal expansion coefficient (Low CTE), low warpage and excellent dimensional stability as an insulating layer. If the amount of the modified filler is too low, the CTE and warpage of the resin film will increase, and the dimensional stability will be poor; if the amount of the modified filler is too high, the chemical copper bonding force of the resin film will be reduced.

[0099] Preferably, the initiator is a free radical initiator.

[0100] Preferably, the initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based free radical initiator, or a combination of at least two of them.

[0101] Preferably, the initiator includes any one of tert-butyl isopropylphenyl peroxide, dicumyl peroxide, benzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 1,1-di(tert-butylperoxy)-3,3,5-dimethylcyclohexane, dicumyl, and polydicumyl, or a combination of at least two thereof.

[0102] Preferably, the thermosetting resin composition further includes 1-50 parts by mass of a flame retardant, for example, the flame retardant may be 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts or 45 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0103] Preferably, the flame retardant includes any one of a halogen flame retardant, a nitrogen flame retardant, a phosphorus flame retardant, and a metal hydroxide flame retardant, or a combination of at least two thereof.

[0104] Preferably, the thermosetting resin composition further comprises other additives, such as a toughening agent and / or a viscosity regulator.

[0105] A solvent may also be added to the above-mentioned thermosetting resin composition, and the amount of the solvent added is selected by a person skilled in the art based on experience and process requirements, so that the thermosetting resin composition reaches a viscosity suitable for use, so as to facilitate the coating of the thermosetting resin composition. The solvent in the thermosetting resin composition will partially or completely volatilize in the subsequent drying, semi-curing or complete curing process.

[0106] The solvent of the present invention is not particularly limited, and generally, ketones such as acetone, butanone, and cyclohexanone, aromatic hydrocarbons such as toluene and xylene, esters such as ethyl acetate and butyl acetate, alcohols such as methanol, ethanol, or butanol, alcohols such as ethyl cellosolve, butyl cellosolve, ethylene glycol monomethyl ether, carbitol, or butyl carbitol, and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, or N-methyl-2-pyrrolidone can be selected; the solvent can be used alone or in combination of two or more. Ketones such as acetone, butanone, and cyclohexanone, and aromatic hydrocarbons such as toluene and xylene are preferred.

[0107] The thermosetting resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the thermosetting resin composition to obtain the thermosetting resin composition.

[0108] In a second aspect, the present invention provides a resin film, wherein the material of the resin film includes the thermosetting resin composition as described in the first aspect.

[0109] Preferably, the resin adhesive film is obtained by coating the thermosetting resin composition on a release material and then drying and / or semi-curing the thermosetting resin composition.

[0110] Specifically, the method for preparing the resin adhesive film comprises: coating the resin adhesive liquid of the thermosetting resin composition on a release material, drying, and removing the release material to obtain the resin adhesive film.

[0111] Preferably, the release material includes any one of a PET release film, a polyethylene film, a polypropylene film or a polyvinyl chloride film.

[0112] Preferably, the thickness of the release material is 10-150 μm, for example, it can be 20 μm, 30 μm, 50 μm, 80 μm, 100 μm, 110 μm, 120 μm, 130 μm or 140 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 20-60 μm is further preferred.

[0113] Preferably, the drying temperature is 80-120°C, for example, it can be 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or 115°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0114] Preferably, the drying time is 1-10 min, for example, it can be 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min or 9 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0115] Preferably, the thickness of the resin film is 10-100 μm, for example, it can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or 90 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0116] In a third aspect, the present invention provides a resin-coated copper foil, wherein the resin-coated copper foil comprises a copper foil layer and a resin layer, wherein the material of the resin layer comprises the thermosetting resin composition as described in the first aspect.

[0117] Preferably, the resin-coated copper foil is obtained by coating the thermosetting resin composition on a copper foil and then drying and / or semi-curing the composition.

[0118] In a fourth aspect, the present invention provides a printed circuit board, wherein the printed circuit board comprises the resin adhesive film as described in the second aspect and / or the resin-coated copper foil as described in the third aspect.

[0119] Compared with the prior art, the present invention has the following beneficial effects:

[0120] (1) In the thermosetting resin composition provided by the present invention, a benzocyclobutene resin, a component containing a C=C unsaturated bond, and a modified filler containing an unsaturated group are compounded, and the unsaturated group in the modified filler plays a bridging role between the interface of the resin component and the inorganic filler, and the benzocyclobutene resin and the component containing a C=C unsaturated bond are fully cured to form a cured product with high crosslinking density and excellent interface consistency. The cured product of the thermosetting resin composition has excellent dielectric properties, a low dielectric loss tangent Df, good dielectric stability, and a small change in ΔDf (10GHz) after HAST.

[0121] (2) The thermosetting resin composition of the present invention is used to prepare a resin film, which has an extremely low dielectric loss tangent Df, Df≤0.00116; the Df change amplitude after HAST (△Df)≤0.00007. At the same time, the resin film has good bonding strength with the metal layer, and the chemical copper bonding strength after Desmear treatment is ≥0.43N / cm, which fully meets the performance requirements of preparing high-frequency and high-speed printed circuit boards by semi-additive method or additive method. BRIEF DESCRIPTION OF THE DRAWINGS

[0122] Figure 1 The infrared spectrum of the benzocyclobutene resin CH-BCB1 provided in Preparation Example 1;

[0123] Figure 2 This is the GPC spectrum of the benzocyclobutene resin CH-BCB1 provided in Preparation Example 1. DETAILED DESCRIPTION

[0124] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0125] In one embodiment, the benzocyclobutene resin is reacted with a hydrocarbon resin and a 4-halogenated benzocyclobutene The hydrocarbon resin includes polybutadiene or styrene-butadiene copolymer, which contains a structural unit of butadiene 1,2-polymerization Hal is a halogen, for example, Cl, Br or I.

[0126] In a specific embodiment, the Hal is Br, that is, the raw material is 4-bromobenzocyclobutene

[0127] In one embodiment, the coupling reaction is carried out in the presence of a palladium catalytic system.

[0128] In a specific embodiment, the palladium catalytic system includes a palladium catalyst and an organic phosphine ligand.

[0129] In a specific embodiment, the palladium catalyst is palladium acetate, and the organic phosphine ligand is tri(o-methylphenyl)phosphine.

[0130] In one embodiment, the coupling reaction is carried out in the presence of an acid binding agent.

[0131] In a specific embodiment, the acid binding agent includes an organic base, more preferably triethylamine.

[0132] In a specific embodiment, the coupling reaction is carried out in an inert protective atmosphere, which includes any one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.

[0133] In a specific embodiment, the coupling reaction temperature is 60-100°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C.

[0134] In a specific embodiment, the coupling reaction time is 5-36 h, for example, it can be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 24 h, 28 h, 32 h or 34 h.

[0135] In a specific embodiment, the preparation of the benzocyclobutene resin further includes an optional hydrogenation step, which can be performed before and / or after the coupling reaction, and can be complete hydrogenation (i.e., all C=C on the main chain and the side chain of the benzocyclobutene resin are hydrogenated, preferably after the coupling reaction) or partial hydrogenation (which can be performed before or after the coupling reaction). The hydrogenation reaction hydrogenates all or part of the C=C double bonds from hydrocarbon resins (e.g., polybutadiene and / or styrene-butadiene copolymers) to form saturated carbon chains (i.e., R1 is ethylene, and / or, R2 is ethyl); thereby, the dielectric properties of the benzocyclobutene resin are further optimized.

[0136] The preparation method of the benzocyclobutene resin is described below in conjunction with a specific preparation example; wherein the specific information of the hydrocarbon resin involved is as follows:

[0137] B2000, polybutadiene, 1,2-polymerized structural units ( The molar percentage of the 1,4-polymerized structural unit ( The molar percentage of 12% (hereinafter the same) is from Nippon Soda Co., Ltd.;

[0138] BI3060, partially hydrogenated polybutadiene resin, 1,2-polymerized structural units 60% by mole, structural units The molar percentage of the polymer is 32%, and the molar percentage of the structural unit formed by 1,4-polymerization is 8%, Nippon Soda Co., Ltd.;

[0139] Ricon 184, butadiene-styrene copolymer, 30% by mole of structural units formed by 1,2-polymerization, 48% by mole of structural units formed by 1,4-polymerization, styrene structural units The molar percentage is 22%, from Sartomer Company, USA.

[0140] Preparation Example 1

[0141] A benzocyclobutene resin CH-BCB1, the preparation method of which is as follows:

[0142] As shown in Table 1, 169.44g 4-bromobenzocyclobutene (4-bromo-BCB), 100g polybutadiene B2000, 16.35g tri(o-methylphenyl)phosphine, 7.48g palladium acetate, 500g triethylamine and 1000g acetonitrile were added to a flask, and the reaction was stirred at 85°C in an argon atmosphere for 24h. Cool and spin-dry the solvent. Use neutral alumina to quickly pass through the column, spin-dry the solvent to obtain a viscous liquid, add 4 times the amount of toluene after toluene dissolves, shake well and let stand, and separate the toluene layer. Then spin-dry and concentrate, and vacuum dry to obtain a colorless viscous liquid, i.e., benzocyclobutene resin CH-BCB1.

[0143] The structure of benzocyclobutene resin CH-BCB1 was characterized by Fourier transform infrared spectrometer (FTIR, IS10 FT-IR, Thermo Fisher Scientific). Figure 1 As shown, from Figure 1 It can be seen that 1473cm -1 The characteristic absorption attributable to the four-membered ring of benzocyclobutene indicates that there is a benzocyclobutene structure in the CH-BCB1 resin. The TLC column shows that the raw material disappears, indicating that the benzocyclobutene structure is completely integrated into polybutadiene.

[0144] According to the record in GB / T 21863-2008, the molecular weight of benzocyclobutene resin CH-BCB1 was tested by gel permeation chromatography (GPC) based on polystyrene calibration. The obtained GPC spectrum is as follows: Figure 2 As shown, Figure 2 3241 is the viscosity average molecular weight of the benzocyclobutene resin CH-BCB1, and its number average molecular weight Mn is 2416.

[0145] Preparation Example 2-3

[0146] A benzocyclobutene resin, which differs from Preparation Example 1 in that the types and amounts of raw materials used are different, as specifically shown in Table 1; the process parameters not shown in Table 1 are the same as those in Preparation Example 1. In Table 1, structural unit A (%), structural unit B (%), and structural unit C (%) are respectively the molar percentages of each in the benzocyclobutene resin; structural unit A (%) and structural unit B (%) are calculated by the feed amount of 4-bromo-BCB and the molar percentage of the 1,2-polymerized structural unit in the resin raw material (thin layer chromatography is used for detection during the preparation process to ensure that 4-bromo-BCB is completely reacted, so that 4-bromo-BCB is completely converted into structural unit A, and the difference between the molar percentage of the 1,2-polymerized structural unit and the structural unit A in the resin raw material is the amount of structural unit B (the corresponding resin raw material is polybutadiene); if the resin raw material is butadiene-styrene copolymer, the molar percentage of structural unit B is the difference between the molar percentage of the 1,2-polymerized structural unit and the structural unit A in the resin raw material plus the molar percentage of the styrene structural unit); structural unit C is derived from hydrocarbon resin (polybutadiene or butadiene-styrene copolymer) and is obtained from the raw material manufacturer.

[0147] Table 1

[0148]

[0149]

[0150] Preparation Example 4

[0151] A modified filler, which is silicon dioxide (spherical silicon powder, D 50 0.5 μm, SO-C2, Japan Admatechs Co., Ltd.), the specific preparation method is as follows:

[0152] 100 parts by mass of spherical silicon powder were placed in a mixer, into which 2 parts of vaporized KBE-503 were sprayed under stirring, and the mixture was reacted for 10 minutes under stirring to obtain a modified filler, which was recorded as F1.

[0153] Preparation Example 5

[0154] A modified filler, which is silicon dioxide (spherical silicon powder, D 50 0.5 μm, SO-C2, Japan Admatechs Co., Ltd.), the specific preparation method is as follows:

[0155] 100 parts by mass of spherical silicon powder were placed in a mixer, into which 0.1 parts of vaporized X-12-1281C were sprayed under stirring, and the mixture was reacted for 10 minutes under stirring to obtain a modified filler, which was recorded as F2.

[0156] Preparation Example 6

[0157] A modified filler, which is silicon dioxide (spherical silicon powder, D 50 0.63 μm, SO-C1, Japan Admatechs Co., Ltd.), the specific preparation method is as follows:

[0158] 100 parts by mass of spherical silicon powder were placed in a mixer, and 1 part of vaporized X-40-2430C was sprayed into the mixer under stirring. The mixture was reacted for 10 minutes under stirring to obtain a modified filler, which was recorded as F3.

[0159] Preparation Example 7

[0160] A modified filler, which is silicon dioxide (spherical silicon powder, D 50 0.63 μm, SO-C1, Japan Admatechs Co., Ltd.), the specific preparation method is as follows:

[0161] 100 parts by mass of spherical silicon powder were placed in a mixer, and 5 parts of vaporized KBM-1403 were sprayed into the mixer under stirring. The mixture was reacted for 10 minutes under stirring to obtain a modified filler, which was recorded as F4.

[0162] Comparative Preparation Example 1

[0163] A modified filler, which is silicon dioxide (spherical silicon powder, D 50 0.5 μm, SO-C2, Japan Admatechs Co., Ltd.), the specific preparation method is as follows:

[0164] 100 parts by mass of spherical silicon powder were placed in a mixer, into which 2 parts of vaporized KBM-573 were sprayed under stirring, and the mixture was reacted for 10 minutes under stirring to obtain a modified filler, which was recorded as F5.

[0165] In the following specific implementation of the present invention, the materials involved are as follows:

[0166] 1. Benzocyclobutene resin

[0167] Benzocyclobutene resins CH-BCB1 to CH-BCB3 provided in Preparation Examples 1-3;

[0168] CYCLOTENE 3022, purchased from The Dow Chemical Company, has the following structure:

[0169]

[0170] 2. Components containing C=C unsaturated bonds

[0171] 2.1 The group containing C=C unsaturated bond is (meth)acrylate group

[0172] MX9000, acrylate-terminated PPO (polyphenylene ether), SABIC, USA;

[0173] Ricacryl 3500, methacrylate-modified polybutadiene, Crayville;

[0174] 2.2 The group containing C=C unsaturated bond is vinyl (CH resin)

[0175] B3000, polybutadiene, Nippon Soda Co., Ltd.;

[0176] Ricon 100, styrene-butadiene resin, Sartomer, USA;

[0177] 2.3 The group containing C=C unsaturated bond is vinylphenyl

[0178] ODV-XET, vinyl aromatic polymer, Nippon Steel Chemical Co., Ltd.;

[0179] OPE-2ST, PPO containing terminal vinylphenyl groups, Mitsubishi Chemical Corporation.

[0180] 2.4 The group containing C=C unsaturated bond is allyl

[0181] Trimethylallyl isocyanate (TMAIC), Hunan Fangruida.

[0182] 3. Initiator

[0183] Tert-butylisopropylphenyl peroxide, BIPB.

[0184] 4. Filler

[0185] Modified fillers F1 to F4 provided in Preparation Examples 4-7;

[0186] The modified filler F5 provided in Comparative Preparation Example 1.

[0187] 5. Flame retardant

[0188] SYTELX 8010, Albemarle, USA.

[0189] Example 1

[0190] A thermosetting resin composition comprises the following components by mass: 20 parts of benzocyclobutene resin CH-BCB1, 30 parts of unsaturated polyphenylene ether MX9000, 30 parts of vinyl aromatic polymer ODV-XET, 20 parts of styrene-butadiene resin Ricon100, 0.35 parts of initiator BIPB, and 200 parts of modified filler F1.

[0191] A resin film and a printed circuit board comprising the thermosetting resin composition, the preparation method of which is as follows:

[0192] (1) Mixing the components of the thermosetting resin composition with toluene according to the above formula to prepare a resin adhesive with a solid content of 65%; coating the resin adhesive on a release film, drying it, and baking it in an oven at 120° C. for 5 minutes to obtain a resin adhesive film with a semi-cured resin layer having a thickness of 40 μm;

[0193] (2) The resin film obtained in step (1) and the browned PCB board are pressed and cured at a curing temperature of 100° C., a pressure of 0.5 MPa, and a time of 1 min. The release film is removed and the surface is treated and copper electroplated to form a laminated printed circuit board with circuits.

[0194] The following performance tests were performed on the resin film and printed circuit board provided in Example 1:

[0195] (1) HAST test

[0196] A Highly Accelerated Temperature and Humidity Stress Test (HAST) was performed according to JESD22-A110 at a temperature of 130° C. and a humidity of 85% RH for 100 h.

[0197] (2) Dielectric loss tangent Df

[0198] Referring to IPC-TM-650 2.5.5.15, the Split Post Dielectric Resonator (SPDR) method was used to measure the dielectric loss tangent Df of the cured resin film at 10 GHz.

[0199] (3) Dielectric loss tangent Df after HAST

[0200] Take the above-mentioned sample with tested Df, and after HAST treatment, use SPDR method to measure the dielectric loss tangent Df of the resin film at 10GHz;

[0201] △Df: Dielectric loss tangent Df after HAST - Dielectric loss tangent Df before HAST.

[0202] (4) Chemical copper bonding strength PS

[0203] The roughened resin film was subjected to the following copper deposition, electroplating and post-curing treatments: soaked in chemical copper solution (MVTP1, ATOTECH) for 20 min—electroplated copper with a thickness of 25 μm—cured in an oven at 200°C for 60 min, and the chemical copper bonding strength of the resin film was tested using a copper foil peel strength tester.

[0204] The test results are shown in Table 2.

[0205] Examples 2-4, Comparative Examples 1-3

[0206] A thermosetting resin composition, a resin film and a printed circuit board comprising the same, which differ from Example 1 in that the formula of the thermosetting resin composition is different, as shown in Table 2; wherein the dosage unit of each component is "part"; the preparation method and performance testing method of the resin film and the printed circuit board are the same as those in Example 1.

[0207] Table 2

[0208]

[0209]

[0210] Combined with the above performance test data, it can be seen that the resin film formed by the thermosetting resin composition prepared by compounding a benzocyclobutene resin with a specific structure, a component containing a C=C unsaturated bond, and an inorganic filler surface-treated with an unsaturated group coupling agent in the present application has low dielectric loss and excellent dielectric stability. It still maintains low dielectric loss after HAST, and has strong bonding with the metal layer, with Df of 0.00102-0.00116, △Df of 0.00005-0.00007 after HAST, and chemical copper bonding of 0.43-0.48N / cm, which can fully meet the requirements of preparing high-frequency and high-speed printed circuit boards by semi-additive method or additive method.

[0211] In Comparative Example 1, an inorganic filler surface treated with an aminosilane coupling agent is used. The inorganic filler surface has no unsaturated groups and cannot play a bridging role between the interface of the unsaturated resin component and the inorganic filler. The filler and the resin interface crosslinking density in the obtained thermosetting resin composition is low, and it is difficult to maintain low dielectric loss after HAST. The ΔDf after HAST is as high as 0.00042. Comparative Example 2 does not use a benzocyclobutene resin with a specific structure, and the obtained thermosetting resin composition has poor dielectric properties, and the dielectric loss is as high as 0.00227. In Comparative Example 3, polybutadiene and 4-bromobenzocyclobutene are directly used and physically mixed, and then other components identical to those in Example 1 are added. Since benzocyclobutene is not grafted into polybutadiene, 4-bromobenzocyclobutene is basically volatilized during the heating precuring process, resulting in the deterioration of the dielectric properties of Comparative Example 3, with Df as high as 0.00294 and ΔDf as high as 0.00034 after HAST.

[0212] The applicant declares that the present invention uses the above embodiments to illustrate the thermosetting resin composition, resin film and application of the present invention, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A thermosetting resin composition, characterized in that The thermosetting resin composition comprises the following components in parts by mass: The modified filler is an inorganic filler that has been surface-treated with an unsaturated group-containing coupling agent, and the unsaturated group in the unsaturated group-containing coupling agent is selected from any one of styrene, acryloxy, methacryloxy, and polybutadiene groups, or a combination of at least two thereof; The benzocyclobutene resin comprises at least one structural unit A and at least one structural unit B; The structural unit A has a structure as shown in Formula I: R1 is vinylene and / or ethylene; The structural unit B has a structure as shown in Formula II: R2 is vinyl, ethyl and / or phenyl.

2. The thermosetting resin composition according to claim 1, characterized in that The unsaturated group-containing coupling agent includes any one of a styrene-containing silane coupling agent, an acryloxy-containing silane coupling agent, a methacryloxy-containing silane coupling agent, a butadiene polymer-modified silane coupling agent, and a styrene-butadiene polymer-modified silane coupling agent, or a combination of at least two thereof; Preferably, based on 100% of the mass of the inorganic filler, the mass of the unsaturated group-containing coupling agent is 0.1-5.0%.

3. The thermosetting resin composition according to claim 1 or 2, characterized in that: The inorganic filler includes any one of silicon dioxide, titanium dioxide, zinc oxide, aluminum hydroxide, aluminum oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, zirconium oxide, mica, boehmite, calcined talc, talc, silicon nitride, strontium titanate, barium titanate, and calcined kaolin, or a combination of at least two thereof; Preferably, the median particle size of the inorganic filler is 0.01-10 μm.

4. The thermosetting resin composition according to any one of claims 1 to 3, characterized in that: The molar percentage of the structural unit A in the benzocyclobutene resin is ≥5%, preferably ≥30%, and more preferably 30-60%; Preferably, the molar percentage of the structural unit B in the benzocyclobutene resin is 15-90%; Preferably, the benzocyclobutene resin further comprises a structural unit C, wherein the structural unit C has a structure as shown in Formula IIIA and / or Formula IIIB: Preferably, the molar percentage of the structural unit C in the benzocyclobutene resin is ≤40%, more preferably ≤30%, and even more preferably ≤20%.

5. The thermosetting resin composition according to any one of claims 1 to 4, characterized in that: The number average molecular weight of the benzocyclobutene resin is 2200-20000, preferably 2500-20000.

6. The thermosetting resin composition according to any one of claims 1 to 5, characterized in that: The component containing C=C unsaturated bonds includes small molecule compounds containing C=C unsaturated bonds and / or resins containing C=C unsaturated bonds; Preferably, the group containing a C=C unsaturated bond includes any one of vinyl, vinylphenyl, vinylbenzyl, allyl, (meth)acrylate, isopropenyl, and maleimide, or a combination of at least two thereof; Preferably, the component containing C=C unsaturated bonds includes any one or a combination of at least two of unsaturated polyphenylene ether, polybutadiene, styrene-butadiene copolymer, styrene-butadiene-styrene triblock copolymer, multifunctional vinyl aromatic polymer, vinyl alicyclic polymer, allyl compound, multifunctional vinyl compound, maleimide compound; Preferably, the unsaturated polyphenylene ether is a polyphenylene ether having a terminal group containing a C=C unsaturated bond; Preferably, the allyl compound includes any one of triallyl isocyanurate, trimethallyl isocyanate, triallyl cyanurate, triallyl polyisocyanurate, triallyl cyanurate, and diallyl phthalate, or a combination of at least two thereof; Preferably, the multifunctional vinyl compound includes any one of divinylbenzene, 1,2-bis(p-vinylphenyl)ethane, and multifunctional (meth)acrylate, or a combination of at least two thereof.

7. The thermosetting resin composition according to any one of claims 1 to 6, characterized in that: The initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based free radical initiator, or a combination of at least two thereof; Preferably, the initiator comprises any one of tert-butyl isopropylphenyl peroxide, dicumyl peroxide, benzoyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexyne, 1,1-di(tert-butyl peroxy)-3,3,5-dimethylcyclohexane, dicumyl, and polydicumyl, or a combination of at least two thereof; Preferably, the thermosetting resin composition further comprises 1-50 parts by mass of a flame retardant; Preferably, the flame retardant includes any one of a halogen flame retardant, a nitrogen flame retardant, a phosphorus flame retardant, and a metal hydroxide flame retardant, or a combination of at least two thereof.

8. A resin film, characterized in that: The material of the resin film comprises the thermosetting resin composition according to any one of claims 1 to 7; Preferably, the resin adhesive film is obtained by coating the thermosetting resin composition on a release material and then drying and / or semi-curing the thermosetting resin composition.

9. A resin-coated copper foil, characterized in that: The resin-coated copper foil comprises a copper foil layer and a resin layer, and the material of the resin layer comprises the thermosetting resin composition according to any one of claims 1 to 7.

10. A printed circuit board, characterized in that: The printed circuit board comprises the resin adhesive film as claimed in claim 8 and / or the resin-coated copper foil as claimed in claim 9.

Citation Information

Patent Citations

  • Thermally curable resin composition, insulating film, inter-layer insulating film, multilayer wiring board, and semiconductor device

    CN111372961A

  • Resin composition for high-frequency high-speed copper-clad plate and application thereof

    CN111647247A

  • Benzocyclobutene monomer, benzocyclobutene resin, preparation of benzocyclobutene resin, low-dielectric material and application of low-dielectric material

    CN114736096A

  • Resin for high-frequency and high-speed copper-clad plate and polymerization method thereof

    CN115677940A

  • Resin composition, copper foil with resin and multilayer printed circuit board

    JP2003064268A

Cited By

  • Resin composition and product thereof

    CN120484427A

  • Thermosetting resin and resin composition

    TWI918534B